Implementasi Sistem Keuangan Desa Dalam Transparansi Pengelolaan Alokasi Dana Desa Di Desa Bulak Kabupaten Indramayu: Implementation of the Village Financial System (SISKEUDES) seen from the Dimensions of the Implementation Environment and Policy Content - Siti Nurhaliza; Evi Priyanti; Amelia Ningsih (JOURNAL OF GOVERNMENT SCIENCE, 2022)
The current government prioritizes village development because of the village law that places villages at the forefront of development. Villages are given sources of funds and the authority to manage them themselves in order to improve community welfare. In managing village fund sources, the Government provides a policy for implementing the Village Financial System Application (SISKEUDES). The Village Financial System Application (SISKEUDES) is an application developed by the Financial and Development Supervisory Agency (BPKP) in order to improve the quality of village financial governance. The basis for the government to make a village fund application is Law Number 6 of 2014 concerning Villages. Villages are given the opportunity to pay for their own government administration, expenditures and carry out development to improve the welfare and quality of life of the village community. Management of Village Fund Allocation is very prone to manipulation so that SISKEUDES is considered capable of having a positive impact in terms of village financial management and village funds, besides that, SISKEUDES is also considered to have an impact in terms of time and cost, so as to create a village fund management system. which is transparency and accountability.